Real time optimum trajectory generation for redundant/hyper-redundant serial industrial manipulators. (10th November 2017) - Ayten, Kagan Koray; Sahinkaya, M Necip; Dumlu, Ahmet
This article presents an optimization technique to develop minimum energy consumption trajectories for redundant/hyper-redundant manipulators with predefined kinematic and dynamic constraints. The optimization technique presents and combines two novel methods for trajectory optimization. In the first method, the system's kinematic and dynamic constraints are handled in a sequential manner within the cost function to avoid running the inverse dynamics when the constraints are not satisfied. Thus, the complexity and computational effort of the optimization algorithm is significantly reduced. For the second method, a novel virtual link concept is introduced to replace all the redundant links to eliminate physical impossible configurations before running the inverse dynamic model for the trajectory optimization. The method is verified on a three-degree of freedom redundant manipulator and the result is also demonstrated with computer simulations based on an 8-link planar hyper-redundant manipulator.